2016
DOI: 10.3390/biology5010009
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Local IGF-I in the Bony Fish Immune System

Abstract: A role for GH and IGF-I in the modulation of the immune system has been under discussion for decades. Generally, GH is considered a stimulator of innate immune parameters in mammals and teleost fish. The stimulatory effects in humans as well as in bony fish often appear to be correlated with elevated endocrine IGF-I (liver-derived), which has also been shown to be suppressed during infection in some studies. Nevertheless, data are still fragmentary. Some studies point to an important role of GH and IGF-I parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 92 publications
(151 reference statements)
1
15
0
1
Order By: Relevance
“…The results manifest that administration of supplementary astaxanthin in fish diet greatly elevated the levels of serum GH throughout the separate feeding phases. GH is a pituitary hormone, which plays a multifunctional role in numerous physiological processes such as growth promotion (Chang & Wong, ; Reindl & Sheridan, ), immune system function (Franz et al, ; Yada, ), reproduction (Benedet, Andersson, Mittelholzer, Taranger, & Bjornsson, ; Weber et al, ), osmoregulation (Sakamoto & McCormick, ; Varsamos, Nebel, & Charmantier, ), and behavioural function (appetite and swimming activity) (Devlin, Sakhrania, Tymchuka, Rise, & Goha, ; Hallerman, McLean, & Fleming, ; Jonsson, Johnsson, & Bjornsson, ), some of which may be closely interlinked in an intricate manner. There are no major efforts, thus far, that systematically elucidate the fundamental role of carotenoids in the modulation of fish GH, with only strong evidence linking to environmental and nutritional manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…The results manifest that administration of supplementary astaxanthin in fish diet greatly elevated the levels of serum GH throughout the separate feeding phases. GH is a pituitary hormone, which plays a multifunctional role in numerous physiological processes such as growth promotion (Chang & Wong, ; Reindl & Sheridan, ), immune system function (Franz et al, ; Yada, ), reproduction (Benedet, Andersson, Mittelholzer, Taranger, & Bjornsson, ; Weber et al, ), osmoregulation (Sakamoto & McCormick, ; Varsamos, Nebel, & Charmantier, ), and behavioural function (appetite and swimming activity) (Devlin, Sakhrania, Tymchuka, Rise, & Goha, ; Hallerman, McLean, & Fleming, ; Jonsson, Johnsson, & Bjornsson, ), some of which may be closely interlinked in an intricate manner. There are no major efforts, thus far, that systematically elucidate the fundamental role of carotenoids in the modulation of fish GH, with only strong evidence linking to environmental and nutritional manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the key members of type II SOCS, SOCS1-3 and CISH, have been cloned in grass carp and confirmed to be inducible by GH and serve as the feedback repressors for GH signaling via the JAK 2 /STAT 5 pathway with inhibitory effects on both basal and GH-induced IGF-I gene transcription at the hepatic level (41). In fish models, cytokine induction by microbial/viral infection [e.g., TNFα and interleukins in carp species (42,43)] and IGF-I modulation by cytokines [e.g., TNFα) have been reported [e.g., in immune cells/tissues of trout and sea bass, see (44) for a recent review]. In turbot, bacterial infection is also effective in increasing SOCS3 mRNA levels in various tissues including the liver and SOCS3 over-expression can inhibit TNFα and IL-1β expression in macrophages isolated from the head kidney (45).…”
Section: Introductionmentioning
confidence: 99%
“…Past work provides evidence for cross-talk between the GH and IGF pathways and the immune system (e.g. Heemskerk et al 1999; Yada, 2007; O’Connor et al, 2008; Smith, 2010; Franz et al, 2016). We recently reported that IGF signalling is repressed in rainbow trout (Oncorhynchus mykiss) in response to bacterial and viral infections, with a striking upregulation of IGFBP subtypes that restrict IGFs from IGF-1R, and potentially modify immune function (Alzaid et al, 2016a, 2016b).…”
Section: Introductionmentioning
confidence: 99%